EDUKASI TERKAIT PENYAKIT DIARE DAN PENYIMPANAN OBATNYA KEPADA WARGA RT 04 RW 04 KELURAHAN PENGGILINGAN - Prasetya, Niko; Iskandar, Honey; Maharani Oktavia, Deva; Amalia Ilmiati, Komala; Holila, Holila (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Diarrhea remains one of the leading causes of morbidity and mortality among children, especially in developing countries such as Indonesia. The high incidence rate of diarrhea and the lack of public knowledge became the background for this community service activity. The purpose was to increase public understanding of diarrheal disease as well as the proper use and storage of medications. The method used was a direct educational counseling session held on May 15, 2025, for residents of RT 04 RW 04, Penggilingan Subdistrict, East Jakarta, at MD “Smarts” Primary Clinic. This activity involved 20 participants and included a pre-test, educational material delivery by lecturers and students, an interactive discussion session, and a post-test. Evaluation showed an increase in understanding, particularly on the points that diarrhea can cause death (13% increase) and dehydration (7% increase). These results indicate that the counseling was effective in improving community knowledge regarding diarrhea prevention and treatment. It is expected that similar programs can be carried out continuously to reduce the incidence of diarrhea in the community.